Prospective, Randomized, Intra-subject Controlled Trial Comparing Ultrasound-guided Thread and Mini-open Carpal Tunnel Release - Meaike, Joshua J; Hasley, Ike B; Brault, Jeffrey S; Shin, Alexander Y (Journal of surgical orthopaedic advances, 2025)
The purpose of this study was to evaluate the efficacy and safety of a minimally invasive, ultrasound-guided, incisionless thread carpal tunnel release (TCTR) compared with mini-open carpal tunnel release (MOR) in a prospective, single-institution, randomized, intrasubject controlled study of patients with bilateral carpal tunnel syndrome (CTS). Patients underwent same-day, immediately sequential bilateral carpal tunnel surgery receiving both a TCTR and an MOR, with randomization occurring in reference to the dominant versus non-dominant extremity. Eleven patients with an average age of 49.8 years were followed for 12 months. There were no clinical or statistical differences between the two procedures at multiple postoperative time periods with respect to functional outcome scores, pain, or strength. All but one patient preferred TCTR over MOR, citing quicker recovery and decreased pain. Ultrasound-guided TCTR is safe and effective with similar functional outcomes, pain, and strength compared with a more traditional MOR. (Journal of Surgical Orthopaedic Advances 34(1):031-036, 2025).